Surah An-Nahl 126 dalam Perspektif Pendidikan Islam - Intan Fazira; Khairunissa Khairunissa; Sinar Hafif Yulistia; M. Luthfi Khoiri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Education is a very crucial issue. Education is presented as nothing but a process to optimize human potential, because the human soul is always dynamic, in process, never frozen, and always moves actively to achieve balance within a certain span of time. Islamic education has an educational concept known by several terms,